Hipocrisia e descaso: a sociedade exposta pelos procedimentos narrativos do conto Declaração, de Marcelino Freire - ALVES, Rosembergh da Silva; PÁDUA, Vilani Maria de (Revista Lumen, 2022)
This article analyzes the short story ‘Declaration’, which is found in the book Amar é crime, by the pernambucano author Marcelino Freire. This narrative discusses several themes, among them, the female homosexuality. However, it is worth mentioning its structural analysis. The writing of the story itself absorbed the other themes, making its form. The technique used by Marcelino is refined and leads us to think, because it deals with such a delicate subject without stereotypes, presented through the points of view of the narrative focus. For this, we rely on studies by Dal Farra (1978), Foucault (2001), Leite (2002), Costa (2006), Ferraz (2008), Carvalho (2012), Miranda (2012; 2013), Silva and Stacke (2014), Inácio (2012; 2016), among other theoretical contributions in which we find support for the analysis.